Chronic disease burden among Latino farmworkers in California - Matias, Susana L.; French, Caitlin D.; Gomez-Lara, Alexander; Schenker, Marc B. (Frontiers in Public Health, 2022)
Farmworkers are an essential workforce to maintain California’s extensive agricultural production. However, this mostly Latino, immigrant population is affected by high poverty rates and food insecurity, which increases their risk of chronic diseases. We analyzed clinical and interview data from three studies of Latino farmworkers in California: 1) the Mexican Immigration to California: Agricultural Safety and Acculturation (MICASA), 2) the PASOS SALUDABLES pilot intervention (PASOS Pilot), and 3) the PASOS Study, a cluster-randomized, controlled trial (PASOS RCT). We aimed to determine the prevalence of diet-related chronic health outcomes (obesity, elevated waist circumference, high blood pressure, and high total cholesterol) and identify sociodemographic and socioeconomic factors associated with these conditions in this population. A total of 1,300 participants were included in this study (452 from MICASA, 248 from PASOS Pilot, and 600 from PASOS RCT). Obesity prevalence ranged from 29.2% to 54.5% across samples; elevated waist circumference was observed in 29.4%-54.0% of participants; high blood pressure was detected in 42.0%-45.5% of participants; 23.7%-25.8% of participants had high total cholesterol. Age was positively associated with each health outcome, although not for each sample; each additional year in age increased odds by 3%-9%, depending of the outcome and sample. Women were at higher risk of obesity (one sample) and elevated waist circumference, but at lower risk of high blood pressure and high total cholesterol. Single, divorced or widowed participants (vs. married/living together) had 35% and 47% reduced odds of obesity and elevated waist circumference, respectively. Each additional year living in the US was associated with 3%-6% increased odds of obesity, depending on the sample. Higher household income was associated with a reduction in odds of high total cholesterol up to 76% (one sample). These findings highlight the increased risk of chronic health conditions in Latino farmworkers, in particular for obesity, and among farmworkers who may lack access to health care, which represents a large proportion of this population. Differences in chronic health risks by sex suggest that clinical and public health responses might need to be gender-specific. Expansion of eligibility for supplemental nutrition programs for this low-income population could reduce their disease burden.